Dietary sulfur concentration has no effect on In Vitro fermentative activity of ruminal mixed microorganisms - Uwituze, S.; Hollis, Larry C.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
We previously reported that elevated concentrations of dietary sulfur (0.65% sulfur, dry basis) in finishing diets containing dried distillers grains with solubles decreased dry matter intake and average daily gains of feedlot cattle. Furthermore, high dietary sulfur concentrations yielded lower ruminal concentrations of volatile fatty acids, but were associated with increased ruminal ammonia concentrations and improved total tract digestibility of the diet. The objective of this study was to investigate, in culture tubes, effects of added sulfur on in vitro dry matter disappearance, volatile fatty acid profiles, and ammonia concentrations from substrates containing different sulfur concentrations when fermented by mixed ruminal microorganisms from a steer fed a diet based on corn and alfalfa.
Beef Cattle Research, 2011 is known as Cattlemen’s Day, 2011
Keywords: Beef; Sulfur; In Vitro; Microorganisms; Corn; Alfalfa